Approach to Headache - Bobker, Sarah M.; Safdieh, Joseph E. (Seminars in Neurology, 2021)
There is a very high prevalence of headache in both outpatient and inpatient settings, in the United States and worldwide, due to an abundance of possible causes. Having a practical and systematic approach to evaluating and treating headache is, therefore, key to making the correct diagnosis, or possibly overlapping diagnoses. Taking a thorough and methodical headache history is the mainstay for diagnosis of both primary and secondary headache disorders. Evaluation and workup should include a complete neurological examination, consideration of neuroimaging in specific limited situations, and serum or spinal fluid analysis if indicated. Adopting a diagnostic approach to headache ensures that cannot-miss, or potentially fatal, headache syndromes are not overlooked, while resource-intensive tests are performed only on an as-needed basis.
Keywords: history taking; approach; impact of headache; burden of headache; migraine